Functions of a complex variable - Pathak, Hemant Kumar; Agarwal, Ravi P.; Cho, Yeol Je (CRC Press, Taylor & Francis Group, 2016)
Functions of a Complex Variable provides all the material for a course on the theory of functions of a complex variable at the senior undergraduate and beginning graduate level. Also suitable for self-study, the book covers every topic essential to training students in complex analysis. It also incorporates special topics to enhance students' understanding of the subject, laying the foundation for future studies in analysis, linear algebra, numerical analysis, geometry, number theory, physics, thermodynamics, or electrical engineering.